2021
DOI: 10.1177/03000605211039386
|View full text |Cite
|
Sign up to set email alerts
|

Association between pain and gait instability in patients with lumbar disc herniation

Abstract: Objective To determine whether pain is associated with gait instability in patients with lumbar disc herniation (LDH). Methods This retrospective cross-sectional study used data from electronic medical records. Among patients with lumbar back pain caused by LDH between January 2017 and July 2019, patients that underwent gait analysis were included. LDH was diagnosed using magnetic resonance imaging. An OptoGait photoelectric cell system was used for gait evaluation. Instability was measured using a gait symmet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 30 publications
0
7
0
Order By: Relevance
“…It has previously been reported that individuals with untreated LDH have a different gait compared with healthy controls. 4,20 However, the long-term effects of surgery on gait…”
Section: Gaitmentioning
confidence: 99%
See 1 more Smart Citation
“…It has previously been reported that individuals with untreated LDH have a different gait compared with healthy controls. 4,20 However, the long-term effects of surgery on gait…”
Section: Gaitmentioning
confidence: 99%
“…5 If any tissues or joints involved in gait are injured, eg, in LDH, movement efficiency can be expected to decrease as a result of the disturbance of these complex mechanisms. 20 Microsoft Kinect is a depth camera technology, which tracks human gait by estimation of skeletal joint locations. 7 Kinect is clinically useful to identify gait abnormalities and postural disorders, as well as for tracking progress within patient rehabilitation.…”
Section: Gait Measuresmentioning
confidence: 99%
“…Lumbar disc herniation (LDH) with lumbar instability is a common cause of low back pain, radiculopathy, and/or neurogenic claudication 1,2 . Patients with LDH prefer to choose surgical decompression of the neural elements and stabilize spinal fusion after invalid non‐operative treatment 3,4 .…”
Section: Introductionmentioning
confidence: 99%
“…Lumbar disc herniation (LDH) with lumbar instability is a common cause of low back pain, radiculopathy, and/or neurogenic claudication. 1 , 2 Patients with LDH prefer to choose surgical decompression of the neural elements and stabilize spinal fusion after invalid non‐operative treatment. 3 , 4 Currently, transforaminal lumbar interbody fusion (TLIF) and posterior lumbar interbody fusion (PLIF) are two widely used types of surgery for LDH therapy.…”
Section: Introductionmentioning
confidence: 99%
“…The great length of the walking path and the size of the working area required for over-ground walking, as well as the inability to reproduce the gait conditions are some of the limitations of the system. However, many of the above limitations are eventually canceled out by placing a pair of bars on the sides of a standard treadmill [ 4 , 5 , 6 ]. In this case, the gait analysis can be performed under the standardized conditions that a treadmill can offer (e.g., predetermined and controlled speed, slope, number of steps, etc.)…”
Section: Introductionmentioning
confidence: 99%